Tuberculosis treatment-related adverse events and associated risk factors: Insights from a retrospective cohort in Morocco - Belomaria, Mohamed; El Bakkali , Mohamed; Bouchefra, Said; Bouazza, Ghizlane; Rektouti, Mohamed; Ouhssine, Mohammed (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Tuberculosis (TB) continues to be a substantial global health concern. Treatment for TB typically involves a regimen of multiple drugs. Although first-line anti-TB medications are generally effective, the associated side effects (SE) can cause significant morbidity and may even hinder treatment adherence. This study seeks to assess the side effects of first-line anti-TB drugs in individuals aged 18 to 55 years attending the pneumo-phthisiology department in the Gharb Region of Morocco.Methods: This retrospective study was conducted in the province of Kenitra, Morocco. Data were collected from 189 participants using a simple random sampling method. Two binary logistic models were developed for this study. The first model examined the effect of sociodemographic factors on side effects of antitubercular drugs. The second model investigated the effect of sociodemographic factors on the risk of treatment discontinuation or modification among patients.Results: Among the patients, 37.0% experienced AEs, with the most common being cutaneous (38.57%), gastrointestinal (22.86%), and neurological (10%). Additionally, 21.7% discontinued or modified their treatment. The intensive treatment phase and the first week of therapy were critical periods for the onset of AEs and treatment interruptions. Logistic regression identified several risk factors. Female gender, low socioeconomic status, rural origin, and diabetes were significantly associated with an increased risk of AEs and treatment discontinuation. Conversely, university education and age groups of 26–36 and 37–55 years were protective factors against treatment interruptions. Patients with diabetes had an 8-fold increased risk of AEs, while early AEs (